1959
DOI: 10.1139/f59-002
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition of Sea Water in the Vicinity of the Atlantic Provinces of Canada

Abstract: Samples of sea water from eight locations at the surface around the coast of the Atlantic Provinces of Canada have been analyzed for their content of major and minor chemical constituents. The salt water in the Bras d'Or Lakes of Cape Breton Island, N.S., was different from that in the contiguous Atlantic Ocean and showed evidence of much dilution. The seven other samples examined averaged 17.17‰ for chlorinity and 31.03‰ for salinity. These averages are low for open oceanic waters. The average composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1960
1960
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Sporadic interest in the Bras d'Or Lakes from the 1960s to the 1980s generated a number of studies of contaminants and the chemical oceanography of the Lakes. Young et al (1959) measured the major ion concentrations in water, and concluded that the composition resulted from simple mixing between freshwater and coastal seawater, a conclusion supported by carbonate system and stable isotope measurements made by Mucci and Pagé (1987). Smith and Rushton (1964) measured dissolved oxygen levels in a number of the barachois ponds around the Lakes.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sporadic interest in the Bras d'Or Lakes from the 1960s to the 1980s generated a number of studies of contaminants and the chemical oceanography of the Lakes. Young et al (1959) measured the major ion concentrations in water, and concluded that the composition resulted from simple mixing between freshwater and coastal seawater, a conclusion supported by carbonate system and stable isotope measurements made by Mucci and Pagé (1987). Smith and Rushton (1964) measured dissolved oxygen levels in a number of the barachois ponds around the Lakes.…”
Section: Introductionmentioning
confidence: 93%
“…Creamer et al, 19734. Chou et al, 1999 Early studies of dissolved metal concentrations in Lake waters (Young et al, 1959;Young, 1976) are of little value because of limitations of the analytical techniques. More recently, a small number of dissolved metal concentrations in the Bras d'Or Lakes were measured on two surveys (Strain et al, 2001).…”
Section: Fig 12mentioning
confidence: 99%
“…A full DoE for four parameters will be applied to describe the yield of recovery. Thus, there should be 2 4 = 16 experiments at this stage additionally, since each experiment will be repeatedly conducted three times to get the average results that will require a large number of experiments. Therefore, a simplification was applied to reduce the method to 2 3 = 8 experiments, as described in the next section.…”
Section: Experiments Proceduresmentioning
confidence: 99%
“…Since seas and oceans cover about two-thirds of the Earth's surface [1,2], seawater has been considered a large reserve that contains almost all elements found in the periodic table (even gold, silver, etc.) with different quantities [3,4]. Usually, the production of NaCl via evaporation of seawater (3 -5 o Bé, depending on different countries and continents) will result in a highly condensed mother liquid so call seawater bittern (SWB) (15 -32 o Bé) which is usually treated as waste [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The figures reported by Young, Smith, and Langille (11) for copper and cobalt are of particular significance, as their samples were likewise taken from the sea around the Atlantic provinces of Canada. The average content of copper found by Young, Smith, and Langille agrees well with the mean compiled by Vinogradov (10), and their average cobalt value of 0. respectively.…”
mentioning
confidence: 89%